Optimalisasi Proteksi Relai Arus Lebih Penyulang Kemuning pada Gardu VBRA Di PT PLN (Persero) UP3 Bekasi UID Jawa Barat - Rendya Maulida Ratipramesti; Insani Abdi Bangsa (Jurnal Teknika, 2022)
Protection system is a way that can be done to prevent and minimize the occurrence of damage from disturbances that will occur so that the distribution of electrical energy can be detected immediately. Overcurrent relays are equipment used in protection systems and can signal excess current so that they can detect disturbances in the form of short circuits which can result in damage to equipment in the electricity distribution system, especially at distribution substations. Furthermore, in the distribution of electricity, there are frequent disturbances in the feeder, so the continuity of the distribution of electricity must always be maintained. However, these feeders often experience disturbances, causing random events in the electricity distribution system, resulting in a trip to one feeder line with many distribution substations. Therefore, in terms of optimizing the distribution of electricity, an adequate protection system is absolutely necessary to overcome the occurrence of overcurrent. Optimization of the protection system carried out at the Kemuning feeder VBRA substation, namely by knowing the cause of the disturbance, performing network recovery at distribution substations, checking VBRA substations, repairing and setting overcurrent relays at VBRA substations, and conducting field trip tests for overcurrent relays at VBRA substations. So that the results obtained that the overcurrent relay can work properly when there is a disturbance in the form of an overcurrent.